A escrita epistolar em interlocução com a vida e a arte : autobiografia de George Sand - Garcia, Dolores Aparecida (2019)
George Sand is the pseudonym of Amandine Aurore Lucile Dupin, born in Paris in 1804, joined the group of novelists writers in nineteenth century France. George Sand wrote his autobiography challenging writers and society at the time. She was one of the most ubiquitous figures in French romanticism, whether as a muse or as the author of extremely influential socialist novels. The story of her life also surprised her by how she addressed her readers, claiming that she was interested only in those who wanted to share with her the sufferings of soul and heart. In a sensitive and critical attitude of thinking things, people and events. It also defended a kind of theory of simplicity, allowing itself to be driven by the mechanisms of memory, and then editing its result. Faced with the challenge, we outlined the purpose of the thesis: to study writer George Sand in her challenging female autobiography in the book History of My Life, divided into five volumes, not for the purpose of making a detailed study of the writer's work, but to verify the intertwining between life and art that resulted in a work that in the nineteenth century changed the image of submission of women George Sand explored, in his writing, paradoxical dimensions of what was then taboo: living the pre-established roles of motherhood, experiencing one's own free sexuality, not worrying about public censorship, confronting various relationships, valuing or defiling religious values. We approach all the confrontations unveiled here taking into account studies prepared by the following authors: Philippe Lejeune (2014), Figueiredo (2013), Gasparini (2004), under the theoretical aspects of autobiography; Butler (2003), Connell (1995), Scott (1995), on gender positions; Daupphin (2002), Diaz (2016) with reflection on the epistolary genre, reading the author's books and Maurois (1956), among others.